Assuring the quality of curriculum, pedagogy and assessment across satellite campuses. Issue 5 (28th May 2019) - Grainger, Peter; Crimmins, Gail; Burton, Kelley
Abstract: Assuring the quality of curriculum, pedagogy and assessment is an increasingly significant issue in higher education. This article explores the potential benefit of 'consensus planning', an ongoing curriculum development, maintenance and monitoring strategy, to achieve consistency of academic standards for student learning and assessment across multiple campuses. This article specifically reports on a 'consensus planning' audit undertaken within the School of Education at a regional university in Queensland that engaged full-time academic staff across two campuses. Results suggest that the success of consensus planning is contingent on the personalities of academics; attitudes towards reaching consensus and top-down policy measures; and geographical proximity of the campuses. To ameliorate some of the barriers to consensus planning it is recommended that higher education institutions build the capacity of academics, supporting them to create curriculum where 'equivalence' is as accepted as 'sameness', and where debate and bottom-up practice and policy recommendation is valued.